Improving Mathematical Problem-Solving Ability Through Models of Problem Based Learning - Yulia Zahara; Nurul Afni Sinaga; Rizka Suhaila; Zurra Yusally Aufa (LPPM Universitas Malikussaleh, 2024)
One of the aims of learning mathematics at school is to develop students' mathematical problem-solving abilities. This is in accordance with the objectives of mathematics learning in the independent curriculum set by the Curriculum and Educational Assessment Standards Agency. In the learning process using the Problem Based Learning model, students will be faced with various mathematical problems which are also related to daily life, so diligent and persistent efforts are needed from students to solve these various problems. This research is experimental research because the researcher applies a treatment to the research sample and then wants to know the effect of this treatment, namely in the form of increasing mathematical problem-solving abilities. The treatment given is learning using the Problem Based Learning model in the experimental class and conventional learning in the control class. The statistical test used to analyze data on increasing mathematical problem-solving abilities is the t* test. Based on the results of the t test, it was found that the sig value was 0.000 < 0.05 so that H0 was rejected, it could be concluded that the average mathematical problem-solving ability of students who receive learning through the problem based learning model is better than students who receive conventional learning.